Suffering from Suffrage: Welfare State Development and the Politics of Citizenship Disqualification. Issue 4 (22nd October 2021) - Andersen, David; Jensen, Carsten; Rasmussen, Magnus B.
Abstract: Following the landmark essay of T. H. Marshall, Citizenship and the Social Class (1949), it has conventionally been assumed that the introduction and expansion of social rights in Europe happened as the final stage of a long process of democratization that included the granting of first civil and then political rights. We present a radically different perspective on the relationship between the extension of suffrage (under meaningful competition for government power) and social rights, that is state-financed entitlements that make citizens' livelihood independent from the labor market in the instance of events such as unemployment or sickness. First, some countries institutionalized a state-financed poor relief system much before mass democratization. In these countries, the primary effect of suffrage extension was to reduce public social spending, not expand it. Second, the way this retrenchment occurred was partly by creating a negative link between social rights, on the one hand, and civil and political rights, on the other. We test our argument with case studies of nineteenth- to early-twentieth-century England, Denmark, Norway, and Prussia, all of which are paradigmatic cases that represent the variation in welfare state types.